Impact of COVID‐19 and partial lockdown on access to care, self‐management and psychological well‐being among people with diabetes: A cross‐sectional study. Issue 8 (21st May 2021) - Yeoh, Ester; Tan, Soon Guan; Lee, Ying Shan; Tan, Hwee Huan; Low, Ying Yee; Lim, Su Chi; Sum, Chee Fang; Tavintharan, Subramaniam; Wee, Hwee Lin
Abstract: Background: The impact of lockdown measures can be widespread, affecting both clinical and psychosocial aspects of health. This study aims to assess changes in health services access, self‐care, behavioural, and psychological impact of COVID‐19 and partial lockdown amongst diabetes patients in Singapore. Methods: We conducted a cross‐sectional online survey amongst people with diabetes with the Diabetes Health Profile‐18 (DHP‐18). Hierarchical regression analyses were performed for each DHP‐18 subscale (Psychological Distress, Disinhibited Eating and Barriers to Activity) as dependent variables in separate models. Results: Among 301 respondents, 45.2% were women, 67.1% of Chinese ethnicity, 24.2% were aged 40 to 49 years, 68.4% have Type 2 diabetes and 42.2% on oral medications alone. During the pandemic and the lockdown, nearly all respondents were able to receive care safely from the clinics they attend (94%) and obtain their medications and diabetes equipment and supplies (97%) when needed. Respondents reported less frequent engagement in physical activity (38%), checking of blood pressure (29%) and blood glucose (22%). Previous diagnosis of mental health conditions (β = 9.33, P = .043), Type 1 diabetes (β = 12.92, P = .023), number of diabetes‐related comorbidities (β = 3.16, P = .007) and Indian ethnicity (β = 6.65, P = .034) were associated with higher psychological distress. Comorbidities were associated with higher disinhibited eating (β = 2.49, P = .014) while ability to reach their doctor despite not going to the clinic is negatively associated with psychological distress (β = −9.50 P = .002) and barriers to activity (β = −7.53, P = .007). Conclusion: Health services access were minimally affected, but COVID‐19 and lockdown had mixed impacts on self‐care and management behaviours. Greater clinical care and attention should be provided to people with diabetes with multiple comorbidities and previous mental health disorders during the pandemic and lockdown.